Mercury and Organic Matter Concentrations in Lake and Stream Sediments in relation to One Another and to Atmospheric Mercury Deposition and Climate Variations across Canada - Mina Nasr; Paul A. Arp (Journal of Chemistry)
This article focuses on analyzing the Geological Survey of Canada (GSC) data for total mercury concentrations (THg) in lake and stream sediments. The objective was to quantify how sediment THg varies by (i) sediment organic matter, determined by loss on ignition (LOI) at 500∘C, (ii) atmospheric Hg deposition (atm.Hgdep) as derived from the Global/Regional Atmospheric Heavy Metals Model GRAHM2005, and (iii) mean annual precipitation and mean monthly July and January temperatures (TJuly, TJan). Through regression analyses and averaging by National Topographic System tiles (NTS, 1:250,000 scale), it was found that 40, 70, and 80% of the sediment THg, LOI, and atm.Hgdep variations were, respectively, related to precipitation, TJuly, and TJan. In detail, lake sediment THg was related to atm.Hgdep and precipitation, while stream sediment THg was related to sediment LOI and TJuly. Plotting sediment THg versus sediment LOI revealed a curvilinear pattern, with highest Hg concentrations at intermediate LOI values. Analysing the resulting 10th and 90th log10THg percentiles within each 10% LOI class from 0 to 100% revealed that (i) atm.Hgdep contributed to the organic component of sediment THg and (ii) this was more pronounced for lakes than for streams.